Model Sistem Pendukung Keputusan Dalam Menentukan Operator Caroline Officer Inbond 188 Terbaik dengan Metode AHP Dan SMART Berdasarkan Rekam Jejak Kinerja Operator - Yan Yang Thanri; Fitri Pranita Nasution (STMIK Budi Darma, 2020)
The Operator Performance Sheet can be used as a standard against which to determine the quality of operator performance. Operator service performance is the spearhead in increasing the number of customers using the product, where the operator is in direct contact with customers to solve and help problems faced by customers. The problem with the telecommunication network agency is the absence of a systemized quality standard for the performance of the 188 inbond caroline officer operator and still uses conventional methods and uses indicators that are unclear and subjective in nature. Where in this way there is a high risk of errors in assessing the performance of the correct operator, plus emotional and familial relationships are often factors that greatly affect the results in evaluating operator performance. From this problem, an operator track record model is needed which is recorded in the Operator Performance Sheet (LKO) as a decision support system model in conducting the performance appraisal process for the operator caroline officer inbond 188 using the AHP and SMART methods. Decision Support System Model with a combination of the application of two methods, namely AHP and SMART, where AHP is used to normalize the weight of the criteria which is used as an indicator in selecting the best operator based on the Operator Performance Sheet which is recorded in the Operator Performance Track Record and the ranking process using the application of the SMART method. looking for utility value based on eleven criteria divided into two parts, namely 2 cost criteria and 11 profit criteria, where the results will be combined with the criteria weights of the AHP method application. This model can be used as a stage or steps and recommendations to agencies, especially leaders, to carry out the selection process for the best inbond 88 caroline officer operator.